“There Is No Cloud”: Toward a Materialist Ecology of Post-Photography - Lager Vestberg, Nina (Captures, 2016)
If the smartphone typifies the post-photographic interface, then the data center epitomizes post-photographic infrastructure. Through critical engagement with cloud computing and its ecological impact on natural environments, this article problematizes the metaphorical conception of ecology in media studies, and argues for a materialist approach to post-photography that takes account of the natural resources and material infrastructures enabling contemporary image practices.